Safeguarding Shariah compliant digital assets for future generations - Abdul Manaf, Zati Ilham; Omoola, Sodiq (2023)
In the digital age, our lives have become increasingly intertwined with technology. Our digital assets, including cryptocurrencies, social media accounts, digital collectibles and online accounts, have become an integral part of our daily lives. A common category of digital assets is for products which are Shariah compliant and tailor-made for Muslim consumers. In this article, DR ZATI ILHAM ABDUL MANAF and DR SODIQ OMOOLA emphasize the importance of a digital estate plan for the protection and proper distribution of digital assets for future generations.